A comprehensive study on buccal mucosal graft urethroplasty: 10 years single surgical unit experience - Ratnakar, Akhilesh; Sharda, Sudesh (International Journal of Research in Medical Sciences, 2017)
Background: The use of Buccal Mucosa Graft (BMG) urethroplasty represents the most widespread method of urethral stricture repair. We present our long-term experience with buccal mucosal grafts, placed either ventrally or dorsally with their short and long term complications. Methods:We repaired 43 bulbar urethral strictures with BMG from 2008 to 2011. Mean patient age was 31 years. The graft was harvested from the cheek under local anaesthesia. The graft was placed on the ventral or dorsal bulbar urethral surface in 18 and 25 cases, respectively. A recurrence even after single attempt of Direct Visual Internal Urethrotomy (DVIU) will be deemed as treatment failure. Data were analyzed using the‘t’ test and Fischer test. Results: Mean stricture length was 5.25 cm (range 1.5 to 9 cm) with mean follow up of 58 months (range 10 to 84 months). Only five patients were found to develop stricture at anastomotic site. Three of them voided normally after single attempt of DVIU. Other two patients (4.65 %) required further open surgery or repeat DVIU during follow up and were considered as failure. Five patients develop wound infection and one presented with urethrocutaneous fistula with no long term donor site complication. Conclusion: With long-term follow-up our series confirms the durability of BMG for the treatment of urethral strictures of more than one centimetre (cm) length with fewer side effects and we conclude that the site of placement of the graft did not affect the outcome.